Estudo de variações bioquímicas e genotoxicidade induzidas por mistura de contaminantes em tilápia (Oreochromis niloticus), como biomarcadores de contaminação ambiental - Rodrigues, Aline Cristina Ferreira [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Water quality is of fundamental importance in ecotoxicological context because the aquatic environments are the main destinations of thousands of chemicals for daily use that can act as potential distorters of these ecosystems. In this context we highlight the pesticides such as organophosphates (OP) and pyrethroid (PI), endocrine disrupters such as 17β-estradiol (E2) and polycyclic aromatic hydrocarbons (PAHs) such as benzo(a)pyrene (BaP). Studies on metabolic responses in organisms subjected to different classes of contaminants are extremely valuable to elucidate the effects of the toxicity of mixtures, known as cocktail effect. The main objective of this study was to evaluate in tilapia (Oreochromis niloticus) the effects of mixtures of BaP, E2, and pesticides diazinon (OP) and cypermethrin (PI) in biomarkers of detoxication, oxidative stress, esterase activity and genotoxic potential. Another objective was to monitor the water quality of the Tietê River that runs through the Araçatuba – SP, sugarcane area of intense activity and nautical condominiums through the same biomarkers, field to apply the methodology used in the laboratory for environmental diagnosis. The concentrations used were 10 μg.L-1 of BaP; 220 μg.L-1 of OP; 0.5 μg.L-1 de PI; 0.5 μg.L-1 of E2 (mixture at low concentration); 100 μg.L-1 BaP, 500 mg.L-1 of OP; 1.5 μg.L-1 of PI; 2.5 μg.L-1 of E2 (mixture at high concentration); 100 μg.L-1 of BaP; 500 μg.L-1 of OP; 1.5 μg.L-1 of PI; 2.5 μg.L-1 of 17 E2. Exposures to the four contaminants mixed for 5 days were preceded, pre-exposure to BaP for 3 days followed by exposure to E2 for 5 days; pre-exposure to E2 for 3 days followed by exposure to BaP for 5 days, and pre-exposure to BaP and E2 individually for 3 days followed by exposure to the pesticide individually and mixed for 5 more days. The activities of glutathione S-transferase and carboxylesterase, and malondialdehyde and reduced glutathione ...

A qualidade da água é de fundamental relevância no contexto ecotoxicológico, pois o os ambientes aquáticos são os principais destinos de milhares de compostos químicos de uso cotidiano, que podem atuar como potenciais deturpadores desses ecossistemas. Nesse contexto se destacam os agrotóxicos, como os organofosforados (OP) e piretróides (PI), os desreguladores endócrinos como o 17β-estradiol (E2) e os hidrocarbonetos policíclicos aromáticos (HPAs) como o benzo(a)pireno (BaP). Estudos que avaliam respostas metabólicas em organismos submetidos a diferentes classes de contaminantes são de extrema valia na tentativa de elucidar os efeitos da toxicidade de misturas, conhecido por efeito cocktail. O objetivo central desse trabalho foi avaliar em tilápia (Oreochromis niloticus) os efeitos de misturas de BaP, do E2, e dos agrotóxicos diazinon (OP) e cipermetrina (PI) em biomarcadores de destoxificação, estresse oxidativo, atividade de esterases e potencial genotóxico. Outro objetivo foi monitorar a qualidade da água do rio Tietê que percorre o município de Araçatuba - SP, região de intensa atividade sulcroalcooleira e de condomínios náuticos, para fins de diagnóstico ambiental. Foram usadas as concentrações de 10 μg.L-1 de BaP; 220 μg.L-1 de OP; 0,5 μg.L-1 de PI; 0,5 μg.L-1 de E2 (mistura em baixa concentração); 100 μg.L-1 BaP, 500 mg.L-1 de OP; 1,5 μg.L-1 de PI; 2,5 μg.L-1 de E2 (mistura em alta concentração) e 100 μg.L-1 de BaP; 500 μg.L-1 de OP; 1,5 μg.L-1 de PI; 2,5 μg.L-1 de 17 E2. Foram realizadas exposições aos quatro contaminantes por 5 dias; pré-exposição ao BaP por 3 dias seguida de exposição ao E2 por 5 dias; pré-exposição ao E2 seguida de exposição ao BaP por 5 dias; e pré-exposição ao BaP e ao E2, individualmente, por 3 dias, seguido de exposição aos agrotóxicos, individualmente e misturados, por mais 5 dias. Foram analisadas a atividade da glutationa S-transferase e ...
Keywords: Ecologia aquatica; Toxicologia ambiental - Tietê, Rio (SP); Toxicologia genética; Tilapia (Peixe) - Efeito da poluição da água; Aquatic ecology